Degradation of Putrescine and Cadaverine in Seawater Cultures by Marine Bacteria - Höfle, Manfred G. (1984)
Marine bacteria removed two diamines, putrescine and cadaverine, from coastal seawater supplemented only with these compounds. Batch cultures of natural bacterial communities were grown in filtered seawater (0.05 μm) supplemented with 500 μg of putrescine or cadaverine per liter. Increases in bacterial cell number were counted with an epifluorescence microscope after acridine orange staining. Removal of diamines from seawater was monitored by high-performance liquid chromatography. Diamines were removed from the seawater cultures within 48 h with no corresponding increase in bacterial yield, growth rate, or viability relative to control (unsupplemented) cultures. Shipboard experiments with open-ocean deep water (1,500 m) showed similar, if slower, removal of putrescine from seawater. Unlike uptake experiments with amino acids, labeled putrescine experiments indicated that most putrescine carbon is mineralized to CO(2) rather than assimilated by the bacteria. After growth in unsupplemented control cultures, the bacteria showed a significant potential to mineralize putrescine, indicating a general degradation potential for this compound by marine bacteria even if the compound was not present during growth. Indicators of metabolic activity such as glucose and glutamic acid uptake and mineralization were not affected by the presence of putrescine. This shows that at the concentrations added, the diamines are not toxic, and therefore detoxification was not the reason for degradation of the diamines by the bacteria.